A Combination Treatment Strategy for Hemorrhagic Shock in a Rat Model Modulates Autophagy - Chu, Xiaogang; Schwartz, Richard; Diamond, Michael P.; Raju, Raghavan Pillai (Frontiers in Medicine, 2019)
Hemorrhagic shock leads to whole body hypoxia and nutrient deprivation resulting in organ dysfunction and mortality. Previous studies demonstrated that resveratrol, dichloroacetate and niacin improve organ function and survival in rats following hemorrhagic shock injury (HI). We hypothesized that a combinatorial formula that collectively promotes autophagy will decrease the dose of individual compounds towards effective therapy for HI. Sprague-Dawley rats were subjected to HI by withdrawing 60% blood volume. NiDaR (Niacin-Dichloroacetate-Resveratrol; 2 mg/kg dose of each) or vehicle was administered following the shock, in the absence of fluid resuscitation, and survival monitored. In order to study alterations in molecular mediators, separate groups of rats were administered NiDaR or vehicle along with resuscitation fluid, following HI. We observed significant improvement (p<0.05) in survival following HI in animals that received NiDaR, in the absence of fluid resuscitation. In NiDaR treated animals that received resuscitation fluid, MAP was significantly increased compared to Veh-treated rats. HI-induced increase in systemic IL-6 levels and tissue expression of IL-6, IL-10, IL-1 and IL-18 genes in the heart were attenuated with NiDaR treatment. NiDaR promoted autophagy following HI as demonstrated by reduced p-mTOR, increased p-ULK1 and p-Beclin. The combinatorial formula, NiDaR, reduced inflammation, promoted autophagy and reduced doses of individual compounds used, and may be more effective in genetically heterogeneous population. In conclusion our experiments demonstrated that the combinatorial drug treatment has salutary effect in rats following HI.